How to attract our future? - perception of plastic surgery among medical students - Odenthal, Jan; Knoedler, Leonard; Özdemir, Berkin; Prantl, Lukas; Machens, Hans-Guenther; Broer, P. Niclas; von Isenburg, Sarah; Rieger, Ulrich M.; Kauke, Martin; Panayi, Adriana C.; Knoedler, Samuel (Journal of plastic, reconstructive & aesthetic surgery, 2023)
Background - There is a mounting body of evidence that underscores the worldwide and US national need for increased plastic surgery recruitment of trainees. Thus, plastic surgery must attract more applicants while maintaining the high-level qualifications of residency candidates. - Methods - A total of 250 (w = 197) medical students rated the prototypical plastic surgeon (PS), general practitioner (GP), and craniomaxillofacial surgeon (CMF) with respect to traits derived from a literature review on the general perception of surgery, favorability, and their intention to pursue a respective career. - Results - Factor analysis yielded two overarching dimensions of prototype perception in addition to femininity and resilience, one reflecting a coldhearted, narcissistic, competitive character (status primacy; SP), and one reflecting role-model-like traits (hard-working, healthy, admired, and empathetic). Prototypical PSs scored significantly higher on SP than GPs (t(249) = 18.72, p < 0.001, d = 1.26) and CMFs (t(249) = 5.73, p < 0.001, d = 0.36), while receiving significantly less positive evaluations (GP: t(249) = -9.93, p < 0.001, d = -0.63; CMF: t(249) = -3.52, p < 0.001, d = -0.22). The higher participants rated PSs on SP, the more likely a career in plastic surgery was excluded (OR = 0.71, p = 0.03). An opposite relationship with femininity approached significance (OR = 1.32, p = 0.06). - Conclusions - Given the growing need for PSs, worldwide and US national task fields have to overcome the outdated traits and highlight the field's pro-bono engagement. Furthermore, plastic surgery should further expand its leading role in promoting female trainees.
Online verfügbar: 24. August 2022, Artikelversion: 15. März 2023
Gesehen am 04.08.2023